Предмет: Алгебра,
автор: bledqq
как это делается?..........
Приложения:
Ответы
Автор ответа:
1
Ответ:
Объяснение: 2a=2(4;-2;3)=(8;-4;6); 0,6b=0,6·(-10;5;-15)=(-6;3;-9);
c=2a+0,6b=(8-6;-4+3;6-9)=(2; -1; -3);
|c|=√2²+ (-1)²+(-3)² =√4+1+9 =√14.
(знак вектора поставь сам)
16,2
n=3(1-2;-3-3) +0,5(-4;2)+2(2;3)- (-5;-1) =(-3;-18)+(-2;1)+ (4;6)- (-5;-1)= (-3-2+4+5; -18+1+6+1)=
(4; - 10 ).
bledqq:
спасибо огромное
Похожие вопросы
Предмет: Английский язык,
автор: Angelinagorozhan
Предмет: Русский язык,
автор: kastodiaMoooo
Предмет: Русский язык,
автор: Ane4ka2011
Предмет: Математика,
автор: пумв
Предмет: Алгебра,
автор: Kateallhate666